Comparison of English Writing Skill between Public and Private Sector Schools Students at Secondary Level: In Pakistani Perspective - Umm e Habiba; Tahira Batool; Sayeda Ayesha (CSRC Publishing, Center for Sustainability Research and Consultancy Pakistan, 2020)
Purpose: The objective of the study was to compare the English writing skills of English in the classroom at secondary level. Design/Methodology/Approach: The study was carried on sample of hundred students of secondary level drawn from simple randomly selected from five private and five public secondary schools of Lahore. Self-structured test was used to compare English writing skill at secondary level. There were two sections of test, essay type and translation of ten sentences into English. The data collected was analyzed by using percentage and results obtained were converted to descriptive findings. Findings: The result showed English writing skill of private school students is better than public schools students because majority of the private school students have correct sentence structure, Subject verb agreement in essay writing, correct Translations of Urdu sentences into English as compared to the public school students. In addition, most of the public schools student's spelling, use of tenses and uses of auxiliaries are good and correct in essay writing rather than the private school students. Implications/Originality/Value: So it is concluded that exercises for the English writing skill may be maximized in both public and private schools by using various teaching techniques.